2017
DOI: 10.1007/s11120-016-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

Transition from exponential to linear photoautotrophic growth changes the physiology of Synechocystis sp. PCC 6803

Abstract: Phototrophic microorganisms like cyanobacteria show growth curves in batch culture that differ from the corresponding growth curves of chemotrophic bacteria. Instead of the usual three phases, i.e., lag-, log-, and stationary phase, phototrophs display four distinct phases. The extra growth phase is a phase of linear, light-limited growth that follows the exponential phase and is often ignored as being different. Results of this study demonstrate marked growth phase-dependent alterations in the photophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 55 publications
3
36
1
Order By: Relevance
“…For the same reason, low cell viability could not account for the decrease in cell division. Our conclusion differs from that of Schuurmans et al (2017), who concluded that the transition to stationary phase is caused by nutrient limitation. However, the authors artificially stopped growth by bubbling cultures with nitrogen gas (N 2 ), which deprived cells of CO 2 and oxygen and, indeed, led to carbon starvation and growth arrest.…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lcontrasting
confidence: 99%
See 1 more Smart Citation
“…For the same reason, low cell viability could not account for the decrease in cell division. Our conclusion differs from that of Schuurmans et al (2017), who concluded that the transition to stationary phase is caused by nutrient limitation. However, the authors artificially stopped growth by bubbling cultures with nitrogen gas (N 2 ), which deprived cells of CO 2 and oxygen and, indeed, led to carbon starvation and growth arrest.…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lcontrasting
confidence: 99%
“…1; Supplemental Table S1). Schuurmans et al (2017) showed that a gradual increase of light intensity can lead cells to divide faster and avoid a linear phase. Based on this observation, the authors affirmed that the decrease of cell division from log to linear phase is caused solely by light limitation (self-shading).…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lmentioning
confidence: 99%
“…To elucidate how the recombinant genes influenced the physiology of the 1,2‐propanediol producing strain Synechocystis PG initial shaking flask experiments have been conducted. Growth phases were distinguished as described by Schuurmans (Schuurmans, Matthijs, and Hellingwerf (). Synechocystis PG and the wild type showed no significant differences in growth during the exponential, linear, and late growth phase (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…; Schuurmans et al . ). For instance, enhanced production is obtained by metabolically active cells in the absence of growth (Berla et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, synthesis of foreign compounds has been shown to compete with natural carbon partitioning in growing cells (Schuurmans et al . ; Giordano and Wang ). The carbon partitioning and product yields differ in various growth phases (Wang et al .…”
Section: Introductionmentioning
confidence: 99%